Preparation and characterization of hydrogels based on biopolymers: FucoPol and Chitin-glucan complex (CGC) - Rodrigues, Thomas Alexandre (2020)
In this thesis, two polysaccharides were produced, FucoPol and chitin-glucan complex (CGC). FucoPol is an exopolysaccharide synthesised by the bacterium Enterobacter A47, composed of fucose, glucose, galactose and glucuronic acid, and also with acyl groups. CGC is a copolymer of chitin and glucan, extracted from the cell wall of the yeast Komagataella pastoris. Both biopolymers were produced using glycerol as the source of carbon, through fed-batch cultivation processes. The gel-forming capacity of these two biopolymers was recently demonstrated, and thus, the aim of this thesis was the production and characterization of FucoPol and CGC based hydrogels in terms of texture, mechanical, viscoelastic, and drug loading and release properties. As FucoPol has the ability to form hydrogels in the presence of some metal cations, different dialysis techniques against Fe3+ solutions were performed to obtain FucoPol hydrogels, as well as different concentrations of iron solutions. On the other hand, CGC solutions obtained by freezing-thawing cycles were subjected to dialysis to induce the polymer’s spontaneous gelation. Different freeze-thaw cycles, freezing time, dialysis temperature, polymer concentration and centrifugation conditions were tested in order to optimize the final properties of CGC hydrogels. All the resulting polymeric structures exhibited high water content (above 95%). The optimized FucoPol hydrogels were more brittle and presented a reduced iron content (below 0.15%), whereas the prevalent ductileness of CGC hydrogels in all the conditions tested provided an easier characterization of texture properties, in which the hydrogel with better hardness (16547 Pa) was obtained with the higher CGC concentration. The ability of CGC hydrogels to load and release model compounds (blue food dye E133/E122, and theophylline 99%) was demonstrated for different gels. However, the drug-release capacity was lower with the increase of CGC concentration. The fact that the resulting hydrogels display different textures, rheological and drug loading and release properties support their use as promising biomaterials in distinct areas including biomedicine, bioremediation, and agriculture.